تغيير الدينار : استجابة لظروف البيئة العراقية (دراسة لتطبيق أنموذج Mosley على العراق) (المجلة العراقية للعلوم الاقتصادية, 2018)
Redenomination is the process of replacing a currency with a new one in specific replacing rate. This process can be achieved by removing zeros or moving the mattress decimal to the left. The studies and researches that focus on redenomination used the Cost-Benefit principal to take decisions about it, but the model that designed by L. Mosley puts seven criteria based on a study of more than sixty processes of redenomination. Those criteria included economic, social and political conditions of the studied countries and in the light of the studies outcome after applying the seven criteria; it will be very clear how appropriate and accurate the denomination fit to the conditions of the selected country. In applying these criteria to the economic, social and political environment of Iraq, they all fall in the direction of redenomination by deleting three zeros; in addition, the study of cost-benefit principal also confirms the same direction. According to the results of the research; the recommendation that came out for the monetary authority and government is to issue a new currency named (New Dinar) to replace the current one in replacing rate (1 new Dinar = 1000 Dinars). The duration of the replacing process will be one year at least, during which the two currencies will be in use together. The redenomination process will start in January 2013 and continue to the end of the mentioned year.